Going Along With It: Neonatal Intensive Care Nurses' Views of a Donor Milk Practice Change. Issue 5 (September 2018) - Miller, Alaina R.; Fenstermacher, Kimberly; Buchko, Barbara L.
Abstract: Background and Purpose: Donor human milk (DHM) is used when a mother's own milk is not available. Donor human milk is available as a frozen pasteurized or commercially sterilized product. An abrupt change in practice in use of donor milk products raised concerns among nurses caring for infants in the neonatal intensive care unit (NICU). The change in practice occurred without the input of nurses and without the sharing of supportive evidence with them. The purpose of this study was to explore NICU nurses' perceptions of the practice change from using frozen pasteurized DHM to using sterilized DHM in this context. Study Design and Methods: A grounded theory study was conducted in a 38-bed Level III NICU. Nurse participants were interviewed using open-ended questions aimed at eliciting their perceptions of using pasteurized and sterilized DHM. Results: There were nine nurse participants. They described their perceptions of feeling confident about pasteurized DHM to feeling uncertain about sterilized DHM. The core category of going along with it was linked to judging DHM based upon attributes, questioning benefits of sterilized DHM, and preferring past practice of using pasteurized DHM . Nurses noted that they could move from feeling uncertain about the practice change to feeling certain if they had evidence to support the practice change. Barriers to seeking evidence were time, knowledge, and waiting for someone else to do it . Clinical Implications: Practice change without interprofessional collaboration is threatened by uncertainty and lack of support for the new practice. Nurses want to give evidence-based care, but they often face barriers to seeking evidence. Removing barriers to evidence-based practice and including nurses as stakeholders in practice change decisions are suggested. Abstract : Nurses working in a level III neonatal intensive care unit experienced a change in practice for feeding preterm infants human breastmilk for which they had no input and were offered little supportive evidence. This study explored nurses' perceptions of the change to sterilized pasteurized donor human milk stored in retort packages and suggestions for a more collaborative approach to adopting new practices and products in the neonatal intensive care unit.